Study of Curcuma diversity from Central Java, Indonesia for sunscreen and antioxidant activity based on quantitative phytochemical analysis - HENNY NURHASNAWATI; REKSI SUNDU; ANITA SUKMAWATI (Society for Indonesian Biodiversity, 2023)
Abstract. Nurhasnawati H, Sundu R, Sukmawati A. 2023. Study of Curcuma diversity from Central Java, Indonesia for sunscreen and antioxidant activity based on quantitative phytochemical analysis. Biodiversitas 24: 6880-6887. Indonesia is home to various plants, including those of the genus Curcuma. This study aimed to determine the effect of total phenolic and flavonoid content of Curcuma on antioxidant activity and SPF values. It is known that this rhizome contains secondary metabolites such as flavonoids and phenols, which are known to have antioxidant potential and are believed to act as natural ingredients for sun protection products. The samples used in this study were rhizomes of five Curcuma species from Central Java, namely C. aeruginosa, C. longa, C. mango, C. xanthorrhiza, and C. zedoaria. Alkaloids, flavonoids and tannins are present in all samples. UV-Vis spectrophotometry was used with the following results: the flavonoid total content ranged from 0.94-243.5 mg QE/g, while the total phenolic from 11.27-109.23 mg GAE/g. The DPPH and ABTS test for antioxidant activity showed that C. longa had the highest activity with an IC50 of 78.79 and 0.4273 ppm. The highest SPF values in C. longa were 31.55-36.97 (high protection). The results of the data analysis using the Spearman correlation test revealed a significant correlation between the antioxidant activity and SPF with the flavonoid and phenolic content of the Curcuma extracts.